Smart and inclusive environments for all - SHAFE explained - Dantas, Carina; van Staalduinen, Willeke; Illario, Maddalena; Spiru, Luiza (Technium Social Sciences Journal, 2021)
The meaning and notion of Smart Healthy Age-Friendly Environments (SHAFE) as a holistic approach that promotes the alignment of policies and strategies across domains is a unique roadmap for the implementation of inclusive communities in and across Europe, improving and supporting independent life throughout its entire course, regardless of age, gender, disabilities, cultural differences and personal choices. When we acknowledge the serious challenges especially those related to demographic change and the COVID-19 pandemic, it is not possible anymore to still work in silos or to keep positions for individual interest. Before any other role, we all are citizens and we have a duty as researchers, academics, policy makers, practitioners, industry and business to work together for a better world. In this paper, the SHAFE concept is explained and an overview of running initiatives is presented. Also the alignment within current policy initiatives of the European Commission is explored and the recognition of SHAFE implemented through NET4Age-Friendly addressed.